2004
DOI: 10.1074/jbc.m401268200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Chlamydia Protein CADD Reveals a Redox Enzyme That Modulates Host Cell Apoptosis

Abstract: The Chlamydia protein CADD (Chlamydia protein associating with death domains) has been implicated in the modulation of host cell apoptosis via binding to the death domains of tumor necrosis factor family receptors. Transfection of CADD into mammalian cells induces apoptosis. Here we present the CADD crystal structure, which reveals a dimer of seven-helix bundles. Each bundle contains a di-iron center adjacent to an internal cavity, forming an active site similar to that of methane mono-oxygenase hydrolase. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 24 publications
1
74
0
Order By: Relevance
“…CADD shares homology with the death domains of tumor necrosis factor family receptors and induces apoptosis when transiently transfected to noninfected cells (36). Although it is not known at present whether CADD is the dominant protein governing apoptosis, a recent study reporting the crystal structure of this protein (35) demonstrated its capability to induce in vivo cell death of HeLa cells. Both catalytic activity and death domain binding were found to be required for its complete biological function.…”
Section: Discussionmentioning
confidence: 99%
“…CADD shares homology with the death domains of tumor necrosis factor family receptors and induces apoptosis when transiently transfected to noninfected cells (36). Although it is not known at present whether CADD is the dominant protein governing apoptosis, a recent study reporting the crystal structure of this protein (35) demonstrated its capability to induce in vivo cell death of HeLa cells. Both catalytic activity and death domain binding were found to be required for its complete biological function.…”
Section: Discussionmentioning
confidence: 99%
“…C. pneumoniae and C. muridarum contain open reading frames encoding hypothetical proteins exhibiting sequence similarity and predicted structural homology to CADD (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…1D), monitoring the m/z ratios corresponding to [M ϩ 2H] 2ϩ and [M ϩ 3H] 3ϩ ions of both peptides. These analyses failed to show any reliable fragmentation compatible with ClpC(7-15) or ClpC (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: One Clpc-derived Ligand Distinct From the Predicted T-cell Ementioning
confidence: 99%
“…1A). EGFP-ClpC fusion proteins were expressed in C1R-B*27:05 cells in order to detect endogenously processed HLA-B27 ligands from this protein, including a predicted T-cell epitope, ClpC (7)(8)(9)(10)(11)(12)(13)(14)(15). Our initial attempts to express the whole ClpC protein using full-length cDNA failed to generate stable C1R transfectants.…”
Section: Expression Of Chlamydial Clpc Fusion Proteins-clpc Is Anmentioning
confidence: 99%